The impact of Ash3 overflow time and indium composition on the formation of self-assembled Inxga1 - Xas quantum dots studied by atomic force microscopy - Aryanto, Didik (2013)
We have performed atomic force microscopy to investigate the effect of various indium compositions and various AsH3 flow times during cooling on the formation of self-assembled InxGa1 xAs quantum dots (QDs). The InxGa1 xAs QDs were grown by metal-organic chemical vapour deposition using the Stranski-Krastanow (S-K) growth mode. The migration of group III species in the growth of InxGa1 xAs QDs is influenced by the AsH3 flow during the cooling period due to the increasing surface population of the active arsenic species. It influences the size and density of the dots on the surface. For various indium compositions, an increase in InxGa1 xAs QD density with increasing indium composition is observed. It indicates that the dot density depends on lattice parameters. The dot density is inversely proportional to surface diffusion (rho [proportional to] R/D), with D = (2kT/h)/a2 exp(ED/kT). In the growth of InxGa1 xAs QDs using the S-K growth mode, the dots were formed on the surface as the effect of elastic strain relaxation due to the lattice mismatch. Increasing indium composition affects the lattice mismatch of the InxGa1 xAs/GaAs QD system, which influences the dot formation on the surface. However, due to the stochastic nature of the nucleation of self-assembled growth, control of the spatial ordering of the QDs has proved to be extremely challenging.